Elite Capture Phenomenon and Political Dialogic Space: Reflections on the Folklore of Asal Usul Raja Negeri Jambi in the Current Political Situation - Zaman, Saefu; Prayoga, Reza Amarta; Sukma, Bayu Permana; Amanat, Tri (Mudra Jurnal Seni Budaya, 2024)
This research focuses on the process of political elite capture which is associated with the current political context and the dialogic space that occurs in the narrative text of the folklore Asal Usul Raja Negeri Jambi (AURNJ) [The Origins of the King of Jambi]. This study used a descriptive qualitative method. The data were obtained from the recording and documentation of Jambi folklore 2: Asal Usul Raja Negeri Jambi (AURNJ) by Kaslani (1997). The results of the analysis produce several conclusions. First, there are symptoms of the political phenomenon of elite capture of village elders in perpetuating their power in the election of the King of Jambi. Second, this phenomenon also fostered the practice of dynastic familism. In the belief of village elders, the king must be chosen from their lineage, meaning that people in their circle are worthy to be king. Third, the deadlock in finding a leader figure was experienced by village elitist elders in the political contestation of the election of the king. This stalemate then awakened the elite village elders to open equal participatory dialogue spaces. This is nothing but to open up opportunities for candidates for kingship outside their circle of power. Fourth, the paradox of elite capture political dynamics in AURNJ's story describes a situation similar to contemporary political phenomena, namely the thirst for power and building political dynasties for personal and group interests as a security strategy and perpetuation of the arena of exposure to power.